ONE-STEP PREPARATION OF PROTEIN A/G-CONJUGATED CdSe/MSA QUANTUM DOTS FOR ULTRAFAST WESTERN BLOT VISUALIZATION (Applied Biological Research, 2023)
Protein A/G (pA/G) has high affinity with the fragment crystallizable (Fc) region of antibodies so is used as a linker to attach antibodies to quantum  dots (QDs), thereby helps the antigen-binding fragment (Fab) to expose  outwardly. The present study deduced the interactive nature between  pA/G and mercaptosuccinic acid-coated CdSe (CdSe/MSA) QDs by using  different reagents to interfere the binding formation. Besides, the use of  pA/G-conjugated QDs (QDs-pA/G) in Western blot was tested by using  QDs-pA/G associated with anti-GST antibodies to label mPrPc-GST  protein in Escherichia coli lysates. The results showed that most of the  pA/G could not bind to QDs in presence of 2% sodium dodecyl sulfate, 0.1  ol and 1% tween 20. The study revealed that pA/G was  mostly bound to CdSe/MSA QDs by non-covalent interactions. The QDs pA/G wassuccessfully applied in direct Western blot with a stronger signal
Keywords: CdSe/MSA; protein A/G (pA/G); Quantum Dots (QDs); Western blot